Isolation and characterization of novel antibacterial compound from an untapped plant, Stereospermum fimbriatum - Awang, Anis Fadhlina Izyani; Ahmed, Qamar Uddin; Ali Shah, Syed Adnan; Md. Jaffri, Juliana; Ghafoor, Kashif; Helaluddin, Abul Bashar Mohammed; Ferdosh, Sahena; Sarker, Md. Zaidul Islam (Taylors & Francis, 2020)
Stereospermum fimbriatum or locally known as “ Chicha ” is traditionally used for itchy skin, earache, stomachache and postpartum treatments. This study was designed to evaluate the antimicrobial potential of S. fimbriatum ’ s stem bark against 11 pathogens and isolate its bioactive compound. Successive soxhlet extraction was conducted using n-hexane, dichloromethane DCM) and methanol. Disc diffusion, minimum inhibitory and bactericidal concentration (MIC & MBC) assays were done to examine the antimicrobial activity. Bioassay-guided isolation was conducted on S. fimbriatum ’ s extract. The DCM extract of stem bark(DS) was the most potent extract followed by n-hexane extract of the stem bark (NS). A novel compound was isolated and coded as C1 which demonstrated potent antibacterial effects with the MIC values as low as 3.13 m g/mL to 6.25 m g/mL, against S. epidermidis,MRSA and S. aureus. Thus, S. fimbriatum could be a potential source of antimicrobial agents for the treatment of skin infections,specifically, MRSA.